2017
DOI: 10.1080/09540121.2017.1281881
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and immune reconstitution among HIV-infected patients on antiretroviral therapy in Nairobi, Kenya

Abstract: Studies on the effects of alcohol use on HIV disease progression have been contradictory, with at least one study finding a positive effect of low alcohol consumption on CD4 count. In addition, most such studies have taken place in the developed West. We investigated the association between alcohol use and immune reconstitution through CD4 count response among HIV-infected individuals on antiretroviral therapy (ART) at an urban sub-Saharan African clinic. This was a retrospective cohort study of treatment-naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The clinical significance of this is that unhealthy alcohol use does not appear to have a direct short-term impact on CD4 cell counts among persons with HIV who are not on ART. This is consistent with several prospective studies conducted in East Africa 18,19,21 and elsewhere, 14,17 but differs from some others. 15,16,20 The gender distribution (68% female) was representative of that of HIV in eastern and southern Africa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The clinical significance of this is that unhealthy alcohol use does not appear to have a direct short-term impact on CD4 cell counts among persons with HIV who are not on ART. This is consistent with several prospective studies conducted in East Africa 18,19,21 and elsewhere, 14,17 but differs from some others. 15,16,20 The gender distribution (68% female) was representative of that of HIV in eastern and southern Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies among persons on ART have found no association between high levels of alcohol use (variously defined as heavy, hazardous, problem, or severe risk alcohol use) and CD4 cell count and/or HIV viral load after controlling for ART adherence. 14,15,17-19 Two recent studies conducted mediation analyses to separate out effects of alcohol use on CD4 cell counts due to reduced adherence versus other pathways. One found direct effects of heavy alcohol use on CD4 cell counts, 20 while the other found only indirect effects of alcohol use via adherence.…”
Section: Introductionmentioning
confidence: 99%
“…This included routine screening or inquiring about alcohol use disorder ( n = 1), and screening and brief intervention (SBI) for AUD ( n = 1) ( Table 2 ). These studies aimed to assess routine screening for alcohol use for people living with HIV during enrollment in the HIV clinic ( 57 ) and implementation of an alcohol screening and brief intervention in 18 primary health care services ( 7 ). The study found nine clinics had good and nine had poor SBI implementation.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we found only two studies that described and reported on the integration status of AUD interventions in general health care settings in SSA (7,57). Importantly, we identified several studies detailing the mental health plans and programs based on integrated interventions for mental health services that include AUD (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning because socioeconomic factors like food insecurity impact adherence to ART and retention in HIV care [146], which has implications for viral suppression and chronic disease pathways [64,147,148]. These factors also have an impact on mental health and may increase susceptibility to alcohol and substance use [149][150][151][152].…”
Section: % Of Participants Were Femalementioning
confidence: 99%